'You're there because you are unprofessional': patient and public involvement as liminal knowledge spaces. Issue 3 (27th December 2017) - Maguire, Kath; Britten, Nicky
Abstract: Patient and public involvement in health research and care has been repeatedly theorised using the metaphor of spaces, knowledge spaces and participatory citizenship spaces. Drawing on data from a three year qualitative study of people involved in health research with organisations across England, this article explores where these spaces fit in a wider social, political and historical landscape. It outlines a theme recurring frequently in the study data: a unified public/patient/service‐user perspective in opposition to a professional/clinical/academic view. This is discussed in relation to Habermas's division between the lifeworld and system. Patient and public involvement is mapped as spaces between these spheres, therefore between the social norms pertaining to them. In this way, involvement spaces are seen as liminal, in‐between or threshold spaces; this concept provides us with new insights on both the opportunities and the conflicts that are integral in the ambiguous, complex interactions which take place in these spaces.